Employing puppet theater in educating children about environmental education, stage Kindergarten (Journal of the College of Basic Education, 2022)
The (puppet theater) is considered one of the most important teaching and educational means, which contributes to the process of implanting and developing the mental, psychological, emotional, social and aesthetic aspects of the child. It directly teaches him the values ​​of his society, environment, habits, and behavior, and works to achieve his goals, tendencies, and directions in building the child in all respects, especially environmental education. In which the child achieves goals and raises a conscious generation